Effects of two modes of Peer Tutoring and Gender on Secondary School Biology Students’ Motivation - Loretta Aniaku, Obiageli; Ibe, Ebere; Chinyere Aham, Assumpta; Ukamaka Ugwu, Theresa; Mariestella Nzewi, Uche (International Journal of Psychosocial Rehabilitation, 2021)
The study examined the effects of two modes of peer tutoring on secondary school Biology students’ motivation. Aptitude Treatment Interaction (ATI) experimental design was used. Three research questions and three null hypotheses guided the study. The population consisted of 2, 636 senior secondary one (SSI) Biology students (10th graders), from 30 public secondary schools. A sample of 224 (109 males and 115 females) students was drawn from three different school types (single –sex male, female and mixed- sex) through simple random sampling. Two intact classes were randomly sampled from each of the three school types and were assigned randomly, to experimental groups I and II. Students in experimental group I were exposed to Reciprocal Peer Tutoring (RPT) while those in experimental group II were exposed to Peer Assisted Tutoring (PAT). Data were collected using Biology Motivation Inventory (BMI) with reliability index of .85 established using Cronbach alpha. Research questions were answered using mean and standard deviations while hypotheses were tested using ANCOVA at 0.05 level of significance. Results obtained indicated that RPT mode promoted students’ motivation in Biology significantly better than PAT mode. The study revealed no significant gender influence and no significant interaction effect of modes of instruction and gender on students’ motivation. The study authenticates Vygotsky’s theory that through child-centered teaching and learning, learners attain their Zone of Proximal Development (ZPD) by problem-solving in collaboration with peers, specifically with more academically brighter peers within heterogenous groups. We recommend that teachers target learners ZPD through child centered teaching and learning such as RPT, in Science (Biology). The strategy supports Deci and Ryan Self–determination theory that striving together by all students’ increases their motivation to learn and persistence in tasks.